The effects of restraint stress and orthodontic tooth movements on the intestinal epithelial structure and metabolic function in rats - Ye Cheng; Yue Li; Ziqing Fan; Nannan Wang; Min Wang; Yanfen Li; Chao Liu; Huang Li; Fuhua Yan (PLoS ONE, 2025)
Chronic stress and orthodontic treatment have been revealed to trigger systemic stress responses in rats. This study aimed to investigate the effects of restraint stress and orthodontic treatment on the intestinal epithelial structure, barrier function, flora, and metabolism in rats. Twenty 8-week-old male Wistar rats were randomly divided into four groups: sham-stressed non-orthodontic (CC), sham-stressed orthodontic (CO), stressed non-orthodontic (SC), and stressed orthodontic (SO). The stress intervention involved subjecting the rats to restraint stress for 21 days, while the orthodontic intervention consisted of maxillary first molar traction from days 8 to 21. Histological and immunohistochemical staining were used to observe the epithelial structure and barrier function of the colon. The intestinal flora and metabolite alterations were investigated by 16S rRNA high-throughput sequencing and untargeted metabolomics sequencing. Colonic epithelial tissue disruption, mucus cells reduction, and a decreased expression of intestinal tight junction proteins were observed in the CO, SC, and SO groups. Lactobacillus spp. abundance was significantly lower in the CO group than in the CC group. Prevotella spp. abundance was significantly lower in the SC and SO groups than in the CC and CO groups. The differential metabolite enrichment pathways between each inter-group comparison might all be related to amino acid biosynthesis, protein digestion and absorption, and cofactor biosynthesis. Both restraint stress and orthodontic treatment may adversely affect the colonic epithelial structure and barrier function of rats. The intestinal flora structure and types of metabolites were also affected cumulatively.